Entre a imagem e a poesia : valorização cultural pelo viés fotopoema - Oliveira, Joelma Márcia Santos de (2018)
This Final Conclusion Paper (FCP) of the Professional Master in Literature, PROFLETRAS, presents a proposal for pedagogical intervention aimed at students of the final series of Elementary School II, from a public school of the municipal educational network of Euclides da Cunha - BA. In general terms, the methodology created involves workshops aimed at reading, critical understanding and elaboration of photopoems, characterized by cultural and regional value. The theoretical orientation behind the proposal brings together the methodological concepts proposed by Rildo Cosson (2011), which deals with the Basic Sequence discussing important issues such as decoding, interpretation, construction of meaning of a text, fundamental stages for literacy literacy effectiveness; those of Joaquim Dolz, Michele Noverraz and Bernard Schneuwly (2004), that approach the Didactic Sequence, a systematic work that allows to the student the dominion of genres and communicative situations; those of Maria Bordini and Vera Aguiar (1988), who, by means of the Receptive Method of reading the literary text, encourage students to read effectively, as they contemplate the readers' textual preferences, but also propose the amplification of these preferences by presenting new readings and / or genres to the students, thus promoting the "rupture of the horizon of expectations". For the implementation of this methodological proposal, we sought practices that contemplated the use of Digital Technologies of Communication and Information (TDIC's), so that the motivation, commitment and skills with the interactive language are positive factors during the suggested teaching-learning process in this dissertation proposal, so the concepts proposed by Roxane Rojo and Eduardo Moura (2012) served as a basis for the multiletramentos that will be treated in this work. As a literary corpus to be worked on in the various stages of the proposal, a meeting of modern and contemporary Brazilian poems and songs was chosen, whose creative conception is at the base of the textual production activity that constitutes the culminating stage of the methodology.